2023
DOI: 10.1002/chem.202300004
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Synthesis of Organic Molecular‐Doped Fluorescent Guanine Crystals with Pearlescence

Abstract: Biomimetic synthesis of guanine crystals has been focused on in the last years. However, multi-functional guanine crystals occluded with fluorescent molecules have not been realized in the laboratory. Here, the controllable synthesis of guanine crystal microplatelets with fluorescence and pearlescence was achieved for the first time by incorporating Nile red (NR) or fluorescein isothiocyanate (FITC) molecules into guanine crystals. The synthesized fluorescent guanine crystals are pure β-phase anhydrous guanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The characteristic absorption peaks of the rhomboidal anhydrous xanthine nanoplates are located at 201 nm and 267 nm in the UV-vis spectra; these are blue-shifted relative to the two characteristic absorption peaks of guanine at 230 nm and 285 nm. 27 The characteristic UV-vis absorption peaks of hypoxanthine are found at 197 nm and 250 nm. 28 The guanine molecule has two main tautomers, N 7 -guanine and N 9 -guanine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic absorption peaks of the rhomboidal anhydrous xanthine nanoplates are located at 201 nm and 267 nm in the UV-vis spectra; these are blue-shifted relative to the two characteristic absorption peaks of guanine at 230 nm and 285 nm. 27 The characteristic UV-vis absorption peaks of hypoxanthine are found at 197 nm and 250 nm. 28 The guanine molecule has two main tautomers, N 7 -guanine and N 9 -guanine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SEM and fluorescence microscope images of synthesized ( c , d ) Nile red- and ( e , f ) fluorescein isothiocyanate-doped guanine platelets (AG β). Copyright 2023, Wiley-VCH [ 50 ]. ( g ) Colorful guanine pearlescent pigment dispersions and solids [ 51 ].…”
Section: Figurementioning
confidence: 99%
“…The remarkable photophysical properties of each of the guanine-based crystal forms, and the fact that they can be selected by easily controlling the experimental conditions employed during crystal synthesis, make this molecule a suitable platform for the development of biomolecule-based materials with interesting optical properties. , In addition, the possibility of modulating the properties of the system through the inclusion of certain molecules in their structure makes guanine-based crystalline materials even more attractive. For instance, very recently Guo et al showed how β-phase anhydrous guanine can be doped with Nile red (NR) or fluorescein isothiocyanate (FITC), as an example of multifunctional guanine crystals occluded with fluorescent molecules obtained in a laboratory …”
Section: Introductionmentioning
confidence: 99%
“…For instance, very recently Guo et al showed how β-phase anhydrous guanine can be doped with Nile red (NR) or fluorescein isothiocyanate (FITC), as an example of multifunctional guanine crystals occluded with fluorescent molecules obtained in a laboratory. 40 Notwithstanding the established fact that guanine-based systems in nature are usually related to structural color and their function is generally complemented or mediated by pigment-containing organelles, 41 studies regarding the direct interaction between guanine and pigment molecules and its relationship with the optical properties, have not been fully explored yet. Even though recent works have shown that structurally similar compounds such as, xanthines and hypoxanthines, could be present in biogenic guanine crystals, 34 several aspects regarding the relationship between guanine and the dopants are still unsolved.…”
Section: ■ Introductionmentioning
confidence: 99%